User acceptance of complex electronic market mechanisms: Role of information feedback. Issue 6 (6th August 2013) - Adomavicius, Gediminas; Curley, Shawn P.; Gupta, Alok; Sanyal, Pallab
Abstract: This paper broadens the scope of evaluating the design of economic mechanisms that is traditionally done solely from an economic perspective. We introduce and demonstrate the application of acceptability to evaluate complex economic mechanisms. In particular, we apply our approach to the evaluation of continuous combinatorial auctions, which represent a complex, sophisticated market mechanism that has not been generally available in the online marketplace but has the potential to enhance the economic efficiency of trade for assets with interdependent values. Such auctions are being increasingly used in industry, e.g., to procure logistical services. Intuitively, acceptance and usage of a complex mechanism can be fostered by a design that provides information and tools that meet the users' task demands. Based on prior research and an analysis of the auction tasks, we discuss practical and innovative information feedback schemes for reducing the cognitive burden of formulating bids in combinatorial auctions. Then, we use constructs from the technology acceptance model (TAM) – which have been consistently shown to be key determinants of technology acceptance in the extant literature – to compare the acceptability of the mechanism under three different information regimes. In addition, we borrow constructs from marketing theory to assess the potential growth in adoption of the mechanism. We compare user perceptions of the three alternative designs in a laboratory experiment with over 130 subjects. Our study constitutes a complementary and novel approach in evaluating the design of complex economic mechanisms. Results indicate a higher adoption and usage potential of the mechanism with advanced information feedback, supporting the potential of combinatorial auctions as a user‐acceptable market mechanism with appropriate feedback.